GE_GERICHTE P/13450/2012 vom 14. Oktober 2024 - GE Cour de justice (2024)
VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);VOIES DE FAIT;ADMINISTRATION DES PREUVES;LÉGITIME DÉFENSE;TENTATIVE(DROIT PÉNAL) | CP.126.al1; CP.139.ch1; CP.144.al1; CP.286.al1; CPP.389.al1; CPP.215.al1.letc; CP.22